Persepsi Siswa SMP Muhammadiyah Boarding School Yogyakarta Terhadap Pembelajaran Bahasa Arab - Linawati, Sri Lestari (Jurnal Dewantara, 2022)
This study aims to, first, determine the perception of students of SMP Muhammadiyah Boarding School (MBS) Yogyakarta of the Arabic language, in terms of two aspects: the level of ease of Arabic and its main function. Second, to determine whether the factors educational background, family background and learning methods can explain students' perceptions about Arabic learning. With the research subjects were students in grade 3 (last class) of SMP MBS Yogyakarta. This study used mixed methods (method mix) with concurrent triangulation strategy, to collect quantitative and qualitative data concurrently, at a time. Furthermore, the two databases were compared to determine whether there is convergence , the differences, or some combination. In this way, mixing occurs when the researchers came to the stage of interpretation and discussion. Analysis of the data showed that the perception of students of SMP MBS Yogyakarta on the level of ease of Arabic language, the majority (65.62 %) stated "simple, but complicated". Learning Arabic since childhood, healthy family relationships, and teaching methods of the Arabic language that promotes the interests of children are the factors that can create a positive perception of the student about Arabic language. About the main function of the Arabic language, the biggest procentage students of SMP MBS Yogyakarta (30,2 %) stated that Arabic language as a means of international communication.